2020
DOI: 10.1016/j.sjbs.2020.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Bioanthropological analysis of human occipital condyles using geometric morphometric method

Abstract: Sex differences are present in all parts of the body, including the skeletal system. Several methods are used to analyze the sex differences of skeleton, while more recently, a new method called geometric morphometry has been used. The aim of this study was to examine the sexual dimorphism of occipital condyles on human skulls originating from the population of Bosnia and Herzegovina using the geometric morphometric method. Material and methods The study was conducted on 214 human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The results of studies conducted on a sample of skulls from the Bosnian population showed the existence of sex differences on different parts of the skull with the application of different methodologies [51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies conducted on a sample of skulls from the Bosnian population showed the existence of sex differences on different parts of the skull with the application of different methodologies [51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%